2013
DOI: 10.3329/bja.v10i2.17282
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Cystic Artery in the Calot’s Triangle and Its Relation with Common Hepatic Duct – a Postmortem Study

Abstract: Results: It was found from the result of the present study that out of 60 cases cystic artery was found as a content of Calot's triangle in 58 (96.65%) cases. Regarding the relations of the cystic artery, out of 60 specimens, in 54 cases (90%) cystic arteries were observed to pass behind the common hepatic duct. In four cases (6.67%) cystic artery were found crossing over the common hepatic duct and in two cases (3.33%), cystic artery were found crossing below the cystic duct.In one cases, branches of cystic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The cystic artery was found inside the calots triangle ranging from 65.0% to 100.0% 5,7,13,14,20,21,23,25 as noted by different investigator where as result of the present study that is 96.67% and it is found to be similar to studies of Desliva 23 and Rahman. 20 As per study of previous authors, the cystic artery was found outside the calot's triangle ranging from 0.0% to 35.0% 7,13,14,20,21,25 as described where as in the present study we recorded as 3.3% (in 1 case).…”
Section: Discussionsupporting
confidence: 87%
“…The cystic artery was found inside the calots triangle ranging from 65.0% to 100.0% 5,7,13,14,20,21,23,25 as noted by different investigator where as result of the present study that is 96.67% and it is found to be similar to studies of Desliva 23 and Rahman. 20 As per study of previous authors, the cystic artery was found outside the calot's triangle ranging from 0.0% to 35.0% 7,13,14,20,21,25 as described where as in the present study we recorded as 3.3% (in 1 case).…”
Section: Discussionsupporting
confidence: 87%
“…Liver and biliary diseases are the most common health problem throughout the world as well as in Bangladesh. The most common biliary diseases are cholelithiasis 5 . Gallstones afflict 10% to 20% of adult populations in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over 20,000,000 persons in the United States have gallstones (Crawford, 2005). Up to 25% of all Bangladeshi people have gallstones 5 . Cholecystitis is associated with cholelithiasis in 95% cases (Crawford, 2005) 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations